N-P double-doped porous carbon supercapacitor electrode material and preparation method thereof

By using N-P double-doped porous carbon supercapacitor electrode material in biomass carbon materials and using dual activation treatments of urea phosphate and K2CO3, the problems of low conductivity and specific surface area of ​​biomass electrode materials are solved, and a high-performance supercapacitor electrode material is achieved.

CN120126944APending Publication Date: 2025-06-10GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510337510.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

When biomass is used as a supercapacitor electrode material, it has poor conductivity, low specific surface area and low electrochemical performance, making it difficult to meet the needs of high-performance energy storage.

Method used

The N-P double-doped porous carbon supercapacitor electrode material is used, and the urea phosphate is used as the dopant and activator, and K2CO3 is used as the secondary activator to achieve dual activation treatment, improving the conductivity and specific surface area of ​​the material.

Benefits of technology

The conductivity, capacitance, pore size distribution uniformity and specific surface area of ​​biomass carbon materials are significantly improved, the electrochemical performance is improved, and the high specific capacitance and good cycling stability are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120126944A_ABST
    Figure CN120126944A_ABST
Patent Text Reader

Abstract

The invention discloses an N-P double-doped porous carbon supercapacitor electrode material which is simultaneously doped with N and P atoms, is of a rich cross-linked microporous carbon nanosheet structure, has a typical amorphous structure and has a relatively high defect degree. The preparation method comprises the following operation steps: S1, mixing the dopant and the xanthoceras sorbifolia bunge seed coat powder according to the mass ratio; s2, primary activation; s3, secondary activation; and S4, washing and drying to obtain the N-P double-doped porous carbon supercapacitor electrode material. A double-activation method is used, the urea phosphate dopant is added to improve the conductivity and capacitance of the biomass carbon material, improve the pore size distribution, increase the specific surface area and improve the surface wettability, and finally, the biomass carbon material is applied to the supercapacitor electrode material, the performance is remarkably improved, and the cycle performance is excellent. 0.5 A / g of the carbon electrode shows excellent capacitance of 414 F / g and has a high specific surface area of 1977 m < 2 > g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and particularly to an N-P dual-doped porous carbon supercapacitor electrode material and a preparation method thereof. Background Art

[0002] With the progress of science and technology, the consumption of energy is increasing continuously. Global warming and the increasing depletion of fossil fuels have forced people to vigorously develop sustainable and renewable energy sources. Renewable energy sources such as solar energy, hydropower, wind energy, and tidal energy are highly anticipated. However, the production of these renewable energy sources is usually affected by natural conditions, making them intermittent and variable. Therefore, it is particularly important to develop efficient and environmentally friendly energy storage technologies. Supercapacitors have become a research hotspot in the energy storage field due to their high power density, long cycle life, and fast charge and discharge capabilities. As an important energy storage technology, supercapacitors have broad application prospects, and continuous research and development will promote their application in various fields. Currently, the materials used as supercapacitor electrodes are mainly of three types: carbon materials, metal oxides, and conductive polymers. Carbon-based materials have good application prospects in electrode materials due to their high specific surface area, low cost, and rich functional groups. Activated carbon is prepared from organic precursors rich in carbon elements through heat treatment (carbonization) and activation treatment in an inert atmosphere. The activation process endows activated carbon with a rich pore structure. These precursors can be obtained from natural renewable resources, such as bagasse, coconut shells, bamboo, and wood chips. According to previous studies, it is known that the doping of carbon materials with heteroatoms (such as nitrogen (N), phosphorus (P), sulfur (S), and oxygen (O)) can improve the conductivity of carbon materials at the chemical level. In addition, the heteroatom functional groups on the surface can provide pseudocapacitance for rapid redox reactions. However, the conductivity of a single carbon material is relatively low, which will lead to a decrease in the electron transfer efficiency, limit the rapid response of the current, and the power density of the capacitor. Therefore, it does not have high performance like other materials (conductive polymers, metal compounds).

[0003] Biomass, as a renewable energy source, can be used as a supercapacitor electrode material. However, when a single biomass is used as a supercapacitor electrode material, there are problems such as limited specific surface area, insufficient conductivity, and uneven pore size distribution. The electrochemical performance is affected by these conditions, resulting in changes in the conductivity and ion diffusion rate of the electrode in the electrolyte, and ultimately leading to low performance, making it difficult to be applied in life. The selection of the activator is also crucial, but most activators have limitations, resulting in a low specific surface area of activated carbon and low electrochemical performance. Summary of the Invention

[0004] To solve the above technical problems, the present invention provides an N-P dual-doped porous carbon supercapacitor electrode material and a preparation method thereof, using urea phosphate as a doping agent and an activator, K2 CO 3 serves as a secondary activator, solving the problems of poor conductivity, low specific surface area, and low electrochemical performance when biomass is used as a supercapacitor.

[0005] To achieve the above object, the technical solution provided by the present invention is as follows:

[0006] An N-P co-doped porous carbon supercapacitor electrode material, which is co-doped with N and P atoms, has a rich cross-linked microporous carbon nanosheet structure and a typical amorphous structure, and has a relatively high degree of defects.

[0007] The preparation method of the above-mentioned N-P co-doped porous carbon supercapacitor electrode material includes the following operation steps:

[0008] S1: Using the Xanthoceras sorbifolia seed coat as the raw material, mixing the dopant and the Xanthoceras sorbifolia seed coat powder in a mass ratio of 1-3:1, then adding water (the purpose of adding water is to mix evenly), and uniformly mixing the mixture of the dopant and the Xanthoceras sorbifolia seed coat powder in water through magnetic stirring, and then drying in an oven to remove moisture;

[0009] S2: Primary activation: In a nitrogen atmosphere, put the product obtained after drying in S1 into a vertical tube furnace and heat it, gradually heating from room temperature to 280-320 °C, lasting for 1.5-2 hours, and naturally cooling to obtain a precursor;

[0010] S3: Secondary activation: Mix the precursor obtained in S1 and potassium carbonate (K 2 CO 3 ) in a mass ratio of 1:2.8-3.2, and grind and mix them using an agate mortar. Put the ground material into a horizontal tube furnace, heat it to 700 °C - 900 °C, and keep it for 1-2 hours, and naturally cool to obtain a pyrolysis product;

[0011] S4: Washing and drying: Carry out overnight pickling on the product obtained in S3, rinse it with deionized water until the pH is neutral, and then dry it to obtain the N-P co-doped porous carbon supercapacitor electrode material.

[0012] Preferably, the dopant in S1 is urea phosphate.

[0013] Preferably, in S2, put the product obtained after drying in S1 into a vertical tube furnace and heat it, gradually heating from room temperature to 300 °C, lasting for 2 hours. Preferably, the heating rate in both S2 and S3 is 5 °C / min.

[0014] Preferably, in S3, put the ground material into a horizontal tube furnace, heat it to 800 °C and keep it for 2 hours.

[0015] Preferably, in S3, mix the precursor obtained in S1 and potassium carbonate (K 2 CO3 ) Mix in a mass ratio of 1:3.

[0016] Preferably, the pickling described in S4 is carried out by cleaning with hydrochloric acid (HCl) with a concentration of 2M; the drying is carried out in a dryer at 80 °C overnight.

[0017] Application of the N-P dual-doped porous carbon supercapacitor electrode material prepared as described above in the electrode prepared from N-P dual-doped porous carbon.

[0018] Electrode preparation and testing: According to the mass percentage, weigh 80% of the N-P dual-doped porous carbon supercapacitor electrode material prepared by the present invention, 10% of polytetrafluoroethylene, and 10% of conductive carbon black, mix them thoroughly with absolute ethanol, apply them to a nickel foam collector, and then press the nickel plate at 5 MPa for 1 minute to prepare a working electrode, and dry it in vacuum at 110 °C for 4 h to finally obtain the electrode prepared from N-P dual-doped porous carbon.

[0019] Assemble a three-electrode system to test the electrochemical performance. The three-electrode system is assembled with 6M KOH as the electrolyte, Pt as the counter electrode, HgO as the reference electrode, and the electrode prepared from N-P dual-doped porous carbon as the working electrode. Then, an electrochemical workstation was used to evaluate the electrochemical performance of the N-P dual-doped porous carbon, including cyclic voltammetry (CV) and galvanostatic charge / discharge (GCD).

[0020] Compared with the prior art, the beneficial effects of the present invention:

[0021] The present invention uses a dual-activation method. By adding a urea phosphate dopant, the conductivity and capacitance of the biomass carbon material are improved, the pore size distribution is improved, the specific surface area is increased, and the surface wettability is improved. Finally, its application in the supercapacitor electrode material results in a significant improvement in performance and excellent cycling performance. The 0.5 A / g carbon electrode exhibits an excellent capacitance of 414 F / g and has a high specific surface area of 1977 m 2 g -1 . Brief Description of the Drawings

[0022] Figure 1 It is the SEM image of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 1.

[0023] Figure 2 It is the Raman spectrum of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 1.

[0024] Figure 3 It is the X-ray powder diffraction pattern of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 1.

[0025] Figure 4 It is the nitrogen adsorption - desorption isotherm of the N - P co - doped porous carbon supercapacitor electrode material prepared in Example 1.

[0026] Figure 5 It is the galvanostatic charge - discharge (GCD) curve of the N - P co - doped porous carbon supercapacitor electrode material prepared in Example 1 at a current density of 0.5 A / g.

[0027] Figure 6 It is the XPS spectrum of the N - P co - doped porous carbon supercapacitor electrode material prepared in Example 1.

[0028] Figure 7 It is the cyclic voltammetry (CV) curve of the N - P co - doped porous carbon supercapacitor electrode material prepared in Example 1 at a scanning rate of 50 mV / s.

[0029] Figure 8 It is the cycling performance of the N - P co - doped porous carbon supercapacitor electrode material prepared in Example 1 under cyclic voltammetry (CV) curve test at a scanning rate of 50 mV / s for 10000 cycles.

[0030] Figure 9 It is the galvanostatic charge - discharge (GCD) curve of the N - P co - doped porous carbon supercapacitor electrode material prepared in Comparative Example 1 at a current density of 0.5 A / g.

[0031] Figure 10 It is the cyclic voltammetry (CV) curve of the undoped porous carbon supercapacitor electrode material prepared in Comparative Example 1 at a scanning rate of 50 mV / s.

[0032] Figure 11 It is the galvanostatic charge - discharge (GCD) curve of the N - doped porous carbon supercapacitor electrode material prepared in Comparative Example 2 at a current density of 0.5 A / g.

[0033] Figure 12 It is the cyclic voltammetry (CV) curve of the N - P co - doped porous carbon supercapacitor electrode material prepared in Comparative Example 2 at a scanning rate of 50 mV / s.

[0034] Figure 13 It is the galvanostatic charge - discharge (GCD) curve of the N - P co - doped porous carbon supercapacitor electrode material prepared in Comparative Example 3 at a current density of 0.5 A / g.

[0035] Figure 14 It is the cyclic voltammetry (CV) curve of the N - P co - doped porous carbon supercapacitor electrode material prepared in Comparative Example 3 at a scanning rate of 50 mV / s.

[0036] Figure 15It is the galvanostatic charge-discharge (GCD) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 3 at a current density of 0.5 A / g.

[0037] Figure 16 It is the cyclic voltammetry (CV) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 3 at a scan rate of 50 mV / s.

[0038] Figure 17 It is the galvanostatic charge-discharge (GCD) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 2 at a current density of 0.5 A / g.

[0039] Figure 18 It is the cyclic voltammetry (CV) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 2 at a scan rate of 50 mV / s.

[0040] Figure 19 It is the galvanostatic charge-discharge (GCD) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 4 at a current density of 0.5 A / g.

[0041] Figure 20 It is the cyclic voltammetry (CV) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 4 at a scan rate of 50 mV / s.

[0042] Figure 21 It is the galvanostatic charge-discharge (GCD) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 5 at a current density of 0.5 A / g.

[0043] Figure 22 It is the cyclic voltammetry (CV) curve of the N-P dual-doped porous carbon supercapacitor electrode material prepared in Example 5 at a scan rate of 50 mV / s. Detailed implementation manners

[0044] The following is a detailed description of the specific implementation manners in conjunction with the accompanying drawings. However, it should be understood that the protection scope of the present invention is not limited by the specific implementation manners. The raw materials and reagents used in the examples are commercially available unless otherwise specified. The Xanthoceras sorbifolia Bunge seed coat powder used in the examples is obtained by grinding commercially available Xanthoceras sorbifolia Bunge seed coat and passing through a 60-mesh sieve.

[0045] The supercapacitor electrode materials prepared in the following examples and comparative examples are all carried out according to the following "Electrode Preparation and Testing":

[0046] Electrode Preparation and Testing: According to the mass percentage, 80% of the N-P dual-doped porous carbon supercapacitor electrode material or supercapacitor electrode material obtained in each of the following examples and comparative examples, 10% of polytetrafluoroethylene, and 10% of conductive carbon black were weighed respectively. After thorough grinding and mixing with absolute ethanol, it was applied to the nickel foam collector, and then the nickel plate was pressed at 5 MPa for 1 minute to prepare the working electrode, and vacuum dried at 110 °C for 4 h. Finally, the electrode made of N-P dual-doped porous carbon or supercapacitor electrode material was obtained.

[0047] Assembled into a three-electrode system to test the electrochemical performance. The three-electrode system was assembled with 6M KOH as the electrolyte, Pt as the counter electrode, and HgO as the reference electrode, and the electrode made of N-P dual-doped porous carbon or supercapacitor electrode material as the working electrode. Then, the electrochemical workstation was used to evaluate the electrochemical performance of N-P dual-doped porous carbon, including cyclic voltammetry (CV) and galvanostatic charge / discharge (GCD).

[0048] Example 1

[0049] A preparation method of an N-P dual-doped porous carbon supercapacitor electrode material, the operation steps are as follows:

[0050] S1: Mix the doping agent urea phosphate and Xanthoceras sorbifolia seed coat powder according to the mass ratio of 2:1, then add water, and uniformly mix the mixture of the doping agent and Xanthoceras sorbifolia seed coat powder in water by magnetic stirring, and then dry in an oven to remove moisture;

[0051] S2 Primary activation: In a nitrogen atmosphere, put the product obtained after drying in S1 into a vertical tube furnace for heating, gradually heat from room temperature to 300 °C at a controlled rate of 5 °C / min, and keep for 2 hours, and obtain the precursor after natural cooling;

[0052] S3 Secondary activation: Mix the precursor obtained in S1 and K 2 CO 3 According to the mass ratio of 1:3, and grind and mix with an agate mortar. Put the ground substance into a horizontal tube furnace and heat it to 800 °C at a heating rate of 5 °C / min, and keep for 2 hours, and obtain the pyrolysis product after natural cooling;

[0053] S4 Washing and drying: Immerse the product obtained in S3 in 2M HCl for overnight pickling, then rinse the product obtained in S3 with deionized water until the pH is neutral, and then dry overnight in a dryer at 80 °C to obtain the N-P dual-doped porous carbon supercapacitor electrode material (NPPC2).

[0054] The electrochemical performance test under the three-electrode system shows that the specific capacitance of this electrode material is 411 F / g at a current density of 0.5 A / g, and it has high electrochemical performance.

[0055] The SEM image of the biomass carbon material obtained in this example is as Figure 1 shown, which is a rich cross-linked microporous carbon nanosheet structure. The Raman spectrum is as Figure 2 shown, with a relatively high degree of defects. These defects are beneficial for ion storage, thereby improving the specific capacitance of the material. The X-ray powder diffraction pattern is as Figure 3 shown. The broad diffraction peak at 21° and the weak diffraction peak near 44° correspond to the (002) and (100) planes of graphite respectively. All the prepared porous carbons have a typical amorphous structure. The XPS is as Figure 6 shown. The complete XPS spectrum shows three main characteristic peaks of C1s, N 1s, and O 1s, as well as a relatively weak P 2p, which confirms the presence of C, N, O, and P elements.

[0056] Nitrogen adsorption-desorption isotherm: The total pore specific surface area was measured under N 2 atmosphere (conventional, 77K). The degassing temperature was 800 °C and the degassing time was 6 h. The nitrogen adsorption-desorption isotherm is as Figure 4 shown, showing typical type I and type IV isotherms. This indicates the presence of micropores, mesopores, and macropores in the carbon material, and the addition of dopants and activators enriches the pore structure of the carbon material.

[0057] Electrochemical test: The N-P dual-doped porous carbon supercapacitor electrode material (80 wt%), polytetrafluoroethylene (10 wt%), and conductive carbon black (10 wt%) prepared in Example 1 were thoroughly ground and mixed with absolute ethanol, and then applied to a nickel foam collector. Then, the nickel plate was pressed at 5 MPa for 1 minute to prepare a working electrode, and vacuum dried at 110 °C for 4 h. Finally, an electrode made of N-P dual-doped porous carbon was obtained. Then, a three-electrode system was assembled to test the electrochemical performance. The three-electrode system was assembled with 6 M KOH as the electrolyte, Pt as the counter electrode, HgO as the reference electrode, and the electrode made of N-P dual-doped porous carbon as the working electrode. Then, a constant current charge-discharge was performed using an electrochemical workstation in the voltage window of -1 - 0 V, and a cyclic voltammetry (CV) curve was tested at a scanning rate of 50 mV / s in the voltage window of -1 - 0 V.

[0058] The galvanostatic charge-discharge (GCD) curve at a current density of 0.5 A / g is as Figure 5 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 7 shown. Its rich and uniform pore structure and heteroatom co-doping show a large closed area, indicating its optimal capacitance performance. The 10,000-cycle performance is as Figure 8 shown, showing extremely high stability and charge-discharge efficiency (about 100% capacitance retention and Coulomb efficiency).

[0059] Example 2

[0060] A preparation method of an N-P dual-doped porous carbon supercapacitor electrode material comprises the following operating steps:

[0061] S1 Mix the dopant urea phosphate and the Xanthoceras sorbifolia Bunge seed coat powder in a mass ratio of 3:1, then add water, and uniformly mix the mixture of the dopant and the Xanthoceras sorbifolia Bunge seed coat powder in water by magnetic stirring, and then dry in an oven to remove the moisture;

[0062] The remaining operations are the same as those in Example 1 to obtain the N-P dual-doped porous carbon supercapacitor electrode material.

[0063] The electrochemical performance test under a three-electrode system shows that the specific capacitance of this electrode material is 364 F / g at a current density of 0.5 A / g.

[0064] The constant current charge-discharge (GCD) curve of this example at a current density of 0.5 A / g is as Figure 17 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 18 shown.

[0065] Example 3

[0066] A preparation method of an N-P dual-doped porous carbon supercapacitor electrode material comprises the following operating steps:

[0067] S1 Mix the dopant urea phosphate and the Xanthoceras sorbifolia Bunge seed coat powder in a mass ratio of 1:1, then add water, and uniformly mix the mixture of the dopant and the Xanthoceras sorbifolia Bunge seed coat powder in water by magnetic stirring, and then dry in an oven to remove the moisture;

[0068] The remaining operations are the same as those in Example 1 to obtain the N-P dual-doped porous carbon supercapacitor electrode material.

[0069] The electrochemical performance test under a three-electrode system shows that the specific capacitance of this electrode material is 318 F / g at a current density of 0.5 A / g.

[0070] The constant current charge-discharge (GCD) curve of this example at a current density of 0.5 A / g is as Figure 15 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 16 shown.

[0071] Example 4

[0072] A preparation method of an N-P dual-doped porous carbon supercapacitor electrode material comprises the following operating steps:

[0073] S3 Secondary activation: The precursor obtained in S1 and K2 CO 3 Mix in a mass ratio of 1:3 and grind the mixture using an agate mortar. Place the ground material in a horizontal tube furnace and heat it to 700 °C at a heating rate of 5 °C / min, and hold for 2 hours. After natural cooling, a pyrolysis product is obtained;

[0074] The remaining operations are the same as those in Example 1 to obtain an N-P dual-doped porous carbon supercapacitor electrode material.

[0075] Electrochemical performance tests under a three-electrode system show that the specific capacitance of this electrode material is 324 F / g at a current density of 0.5 A / g.

[0076] The galvanostatic charge-discharge (GCD) curve of this example at a current density of 0.5 A / g is as Figure 19 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 20 shown.

[0077] Example 5

[0078] A preparation method of an N-P dual-doped porous carbon supercapacitor electrode material, the operation steps are as follows:

[0079] S3 Secondary activation: Mix the precursor obtained in S1 and K 2 CO 3 Mix in a mass ratio of 1:3 and grind the mixture using an agate mortar. Place the ground material in a horizontal tube furnace and heat it to 900 °C at a heating rate of 5 °C / min, and hold for 2 hours. After natural cooling, a pyrolysis product is obtained;

[0080] The remaining operations are the same as those in Example 1 to obtain an N-P dual-doped porous carbon supercapacitor electrode material.

[0081] Electrochemical performance tests under a three-electrode system show that the specific capacitance of this electrode material is 324 F / g at a current density of 0.5 A / g.

[0082] The galvanostatic charge-discharge (GCD) curve of this example at a current density of 0.5 A / g is as Figure 21 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 22 shown.

[0083] Comparative Example 1

[0084] A preparation method of a supercapacitor electrode material, the operation steps are as follows:

[0085] S1 Mix the dopant urea phosphate and the Xanthoceras sorbifolia Bunge seed coat powder at a mass ratio of 0:1, add water, mix the Xanthoceras sorbifolia Bunge seed coat powder in water by magnetic stirring, and then dry it in an oven to remove the moisture;

[0086] The remaining operations are the same as those in Example 1 to obtain the supercapacitor electrode material.

[0087] The electrochemical performance test under the three-electrode system shows that the specific capacitance of this electrode material is 234 F / g at a current density of 0.5 A / g.

[0088] The constant current charge-discharge (GCD) curve of this example at a current density of 0.5 A / g is as Figure 9 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 10 shown.

[0089] Comparative Example 2

[0090] A preparation method of an N-P dual-doped porous carbon supercapacitor electrode material, the operation steps are as follows:

[0091] S1 Mix the dopant urea and the Xanthoceras sorbifolia Bunge seed coat powder at a mass ratio of 2:1, add water, mix the mixture of the dopant and the Xanthoceras sorbifolia Bunge seed coat powder evenly in water by magnetic stirring, and then dry it in an oven to remove the moisture;

[0092] The remaining operations are the same as those in Example 1 to obtain the N-P dual-doped porous carbon supercapacitor electrode material.

[0093] The electrochemical performance test under the three-electrode system shows that the specific capacitance of this electrode material is 283 F / g at a current density of 0.5 A / g.

[0094] The constant current charge-discharge (GCD) curve of this example at a current density of 0.5 A / g is as Figure 11 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 12 shown.

[0095] Comparative Example 3

[0096] A preparation method of an N-P dual-doped porous carbon supercapacitor electrode material, the operation steps are as follows:

[0097] S1 Mix the dopant ammonium phosphate and the Xanthoceras sorbifolia Bunge seed coat powder at a mass ratio of 2:1, add water, mix the mixture of the dopant and the Xanthoceras sorbifolia Bunge seed coat powder evenly in water by magnetic stirring, and then dry it in an oven to remove the moisture;

[0098] The remaining operations are the same as those in Example 1 to obtain the N-P dual-doped porous carbon supercapacitor electrode material.

[0099] The electrochemical performance test under the three - electrode system shows that the specific capacitance of this electrode material is 297 F / g at a current density of 0.5 A / g.

[0100] The galvanostatic charge - discharge (GCD) curve of the obtained product in this example at a current density of 0.5 A / g is as Figure 13 shown, and the cyclic voltammetry (CV) curve at a scanning rate of 50 mV / s is as Figure 14 shown.

[0101] The doping agent urea phosphate in the present invention decomposes into small molecules such as phosphoric acid and urea during the activation process. These small molecules will participate in the pore formation of activated carbon, promoting the development of micropores and the doping of N, O, and P elements; heteroatoms can change the electron - donor properties of carbon materials, thereby improving hydrophilicity and conductivity, and overcoming the drawback of poor conductivity of activated carbon. In addition, these heteroatoms can quickly undergo redox reactions to provide pseudocapacitance. Compared with carbon materials without heteroatom doping, carbon materials with heteroatom doping have better capacitance storage performance.

[0102] Activating biomass materials with a single activator has limitations such as insufficient performance and low specific surface area. For example, when the shell of Xanthoceras sorbifolium is activated with a single activator (K 2 CO 3 )(Comparative Example 1), it only has a performance of 235 F / g and a specific surface area of 1045 m 2 g -1 . The present invention uses a dual - activation method, selects urea phosphate as a doping agent and an activator, and K 2 CO 3 as a secondary activator. The atoms provided by urea phosphate can quickly undergo redox reactions to provide pseudocapacitance. These atoms increase the electron conductivity by increasing the electron density in the p - p conjugate of the carbon matrix, improve the surface wettability, and promote charge transfer through charge modulation, thereby increasing the power and energy density; furthermore, the atoms provided by urea phosphate are beneficial to improving the wettability in aqueous electrolytes and broadening the voltage window. The doping surface wettability will be significantly improved, and the contact angle with water will decrease. The sample prepared by the two - way pore formation of K 2 CO 3 and urea phosphate has a three - dimensional porous network structure, and the doping of heteroatoms adjusts the disorder and defects of the material, thereby promoting the formation of surface pseudocapacitance. Therefore, the carbon electrode at 0.5 A / g exhibits an excellent capacitance of 414 F / g and a high specific surface area of 1977 m 2 g -1 . Obviously, the addition of urea phosphate improves the specific surface area wettability, conductivity, capacitance, and other physical and chemical properties of the biomass - based material, and finally significantly improves the electrochemical performance of the carbon material.

[0103] The foregoing description of the specific exemplary embodiments of the present invention is for purposes of illustration and exemplification; these descriptions are not intended to limit the invention to the precise forms disclosed, and it is apparent that many changes and variations are possible in light of the above teachings; the purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the invention and its practical application, so that those skilled in the art can implement and utilize the various different exemplary embodiments of the invention, as well as various different selections and changes; the scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A NP dual-doped porous carbon supercapacitor electrode material, characterized in that: NP dual-doped porous carbon supercapacitor electrode materials are doped with N and P atoms at the same time. They are rich cross-linked microporous carbon nanosheet structures with typical amorphous structures and a high degree of defects.

2. A method for preparing the NP dual-doped porous carbon supercapacitor electrode material as claimed in claim 1, characterized in that: The following steps are included: S1: mixing the doping agent and the Xanthoceras sorbifolia seed coat powder in a mass ratio of 1 to 3:1, adding water, mixing the doping agent and the Xanthoceras sorbifolia seed coat powder uniformly in the water by stirring, and then drying; S2 primary activation: In a nitrogen atmosphere, the product obtained after drying S1 is heated to 280-320°C for 1.5-2 hours, and then cooled to obtain a precursor; S3 secondary activation: the precursor obtained in S1 and potassium carbonate are mixed in a mass ratio of 1:2.8-3.2, and ground and mixed, the ground material is heated to 700°C to 900°C, and maintained for 1-2 hours, and a pyrolysis product is obtained after cooling; S4 washing and drying: The product obtained in S3 is acid-washed overnight, rinsed with water until the pH is neutral, and then dried to obtain the NP dual-doped porous carbon supercapacitor electrode material.

3. The method for preparing the NP dual-doped porous carbon supercapacitor electrode material according to claim 1, characterized in that: The dopant in S1 is urea phosphate.

4. The method for preparing the NP dual-doped porous carbon supercapacitor electrode material according to claim 1, characterized in that: In S2, the product obtained after drying in S1 is heated to 300°C for 2 hours. Preferably, the heating rates in S2 and S3 are both 5°C / min.

5. The method for preparing the NP dual-doped porous carbon supercapacitor electrode material according to claim 1, characterized in that: In S3, the ground material is heated to 800°C and maintained for 2 hours.

6. The method for preparing the NP dual-doped porous carbon supercapacitor electrode material according to claim 1, characterized in that: In S3, the precursor obtained in S1 and potassium carbonate are mixed in a mass ratio of 1:

3.

7. The method for preparing the NP dual-doped porous carbon supercapacitor electrode material according to claim 1, characterized in that: The acid washing in S4 is performed by using 2M hydrochloric acid; the drying is performed by drying at 80° C. overnight.

8. Use of the NP dual-doped porous carbon supercapacitor electrode material according to any one of claims 1 to 7 in preparing NP dual-doped porous carbon electrodes.

9. The use of the NP dual-doped porous carbon supercapacitor electrode material according to claim 8 in preparing NP dual-doped porous carbon electrodes, characterized in that: The electrode is prepared by weighing 80% of the NP dual-doped porous carbon supercapacitor electrode material prepared by the present invention, 10% of polytetrafluoroethylene and 10% of conductive carbon black according to mass percentage, mixing them with anhydrous ethanol, applying them to a foam nickel collector, and then pressing the nickel plate at 5 MPa for 1 minute to prepare a working electrode, and vacuum drying at 110°C for 4 hours to finally obtain an electrode made of NP dual-doped porous carbon.